Efetividade da órtese noturna no tratamento da dor em mulheres com osteoartrite sintomática nas articulações interfalângicas : estudo controlado e randomizado - Silva, Paula Gabriel [UNIFESP] (2017)
Objective: Evaluate the effectiveness of night orthoses for II and III or fingers of the dominant hand in women diagnosed with symptomatic interphalangeal osteoarthritis. Methods: This is a randomized, controlled, independent value, intention to treat and follow-up of six months. Fifty-two women were randomized into two groups, one group used the night orthoses custom of thermoplastics for the II and III or fingers, the control group did not use the orthoses during the study; both received educational session on hand OA. The evaluations were performed at four times: T0, T45, T90 and T180 days after enrollment. Variables studied: pain at rest and activity in fingers, handgrip and pinch strength, function by Cochin and AUSCAN questionnaires and manual performance by test pick-up. Results: The groups showed a different behavior over time with reduced values for pain at rest, pain on activity and total values of AUSCAN and Cochin questionnaires, statistically significant in favor of the orthoses group. The orthoses group decreased pain at rest in 2.1 cm (p = 0.002) and pain in activity at 4.3 cm (p <0.001). Improving pain showed a moderate correlation with the Cochin questionnaire and Bouchard’s nodes presence in III finger presented as a factor of worse prognosis predictor for pain reduction in the treatment of orthoses. Conclusion: The night orthoses demonstrated effectiveness in the treatment for reducing pain in II and III fingers and improved function in women with symptomatic osteoarthritis of the dominant hand.